Fujita Exponent for a Nonlinear Degenerate Parabolic Equation with Localized Source - Yulan Wang; Xiaojun Song; Chao Ye (Advances in Mathematical Physics)
This paper is devoted to understand the blow-up properties of reaction-diffusion equations which combine a localized reaction term with nonlinear diffusion. In particular, we study the critical exponent of a p-Laplacian equation with a localized reaction. We obtain the Fujita exponent qc of the equation.